2003
DOI: 10.1046/j.1464-410x.2003.04270.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel surveillance protocol for stage I nonseminomatous germ cell testicular tumours

Abstract: RESULTSThe median (range) follow-up was 38 (6-265) months; the relapse rate was 24% and all occurred before 23 months, with 87% diagnosed within the first year. Platinumbased chemotherapy was given to patients with relapse, and surgery used after chemotherapy in seven. Among all the risk factors, an embryonal carcinoma component was the only significant predictor of relapse. The overall survival rate was 99%. CONCLUSIONThe presence of embryonal carcinoma in the primary pathology is the only risk factor determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…As well as the percentage of embryonal carcinoma as a core data item, the approximate percentages of other tumour elements should be given. LVI, embryonal carcinoma and yolk sac tumour were risk factors for relapse in a study of 132 patients . A second study showed that 25 of 85 men who had predominantly embryonal carcinoma histology relapsed .…”
Section: Methodsmentioning
confidence: 96%
“…As well as the percentage of embryonal carcinoma as a core data item, the approximate percentages of other tumour elements should be given. LVI, embryonal carcinoma and yolk sac tumour were risk factors for relapse in a study of 132 patients . A second study showed that 25 of 85 men who had predominantly embryonal carcinoma histology relapsed .…”
Section: Methodsmentioning
confidence: 96%
“…Various studies have been designed to reduce the number of CT scans during the surveillance strategy [31,32]. The prospective-randomized Medical Research Council Trial TE08 was initiated which compared the diagnostic efficacy of two versus five CT scans during the first 2 years of follow-up to detect the number of patients who have intermediate and poor prognosis disease at relapse [32].…”
Section: Active Surveillancementioning
confidence: 99%
“…The study concluded that the presence of embryonal carcinoma component was the only significant risk factor that could determine disease relapse. [38] Another group that evaluated 10-year results of a surveillance study of clinical stage I non-seminomatous cancer showed that 25 of 85 men experienced relapse after a median disease-free interval of seven months. [39] All 25 patients had predominant embryonal carcinoma histology in their primary tumor which was significantly associated with disease relapse (p=0.008).…”
Section: Embryonal Carcinoma Histologymentioning
confidence: 99%